MANDAT BUDAYA DALAM WAWASAN DUNIA KRISTEN: SUATU KRITIK TERHADAP DUALISME - Vivian Sadikin; Yohanes Hasiholan Tampubolon (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
Cultural engagement is not an option but a duty. This article discusses the cultural mandate used to criticize the separation between sacred and secular. The cultural mandate will be explained through definitions and theological reviews found in various literature. Then, the author will show their critique of the separation between sacred and secular based on their understanding of the cultural mandate within the Christian worldview. This research article uses the library research method. This method will examine previous findings on the dualistic worldview and the cultural mandate from various literary sources such as books, academic journals, and online news with a narrative review approach. The result highlights the importance of understanding the cultural mandate within the cosmic context of the Bible's metanarrative (Creation-Fall-Redemption) as a strong foundation to reject this sacred and secular dualism. Every Christian needs to understand that they no longer need to live in a world that is separated between sacred and secular, but they can dedicate their entire life to Christ for the glory of God.